2019
DOI: 10.3390/ijms20133283
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Iron Overload and Ferroptosis on Reproductive Disorders in Humans: Implications for Preeclampsia

Abstract: Iron is an essential element for the survival of most organisms, including humans. Demand for iron increases significantly during pregnancy to support growth and development of the fetus. Paradoxically, epidemiologic studies have shown that excessive iron intake and/or high iron status can be detrimental to pregnancy and is associated with reproductive disorders ranging from endometriosis to preeclampsia. Reproductive complications resulting from iron deficiency have been reviewed elsewhere. Here, we focus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 152 publications
(209 reference statements)
1
92
0
Order By: Relevance
“…Ferroptosis, as a regulated cell death phenomenon, was first reported in 2012, and is a type of iron-dependent lipid peroxidation ( 5 ). With the advancements in research, ferroptosis has been reported to play a role in the development of blood diseases, neurological diseases, respiratory diseases, cardiovascular diseases, reproductive system diseases and tumors ( 28 - 32 ). However, the related reports of the role of ferroptosis in urinary system diseases have mainly focused on renal failure and renal tumors ( 18 , 22 ), and to date, there is no relevant report available on the topic of urolithiasis, at least to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis, as a regulated cell death phenomenon, was first reported in 2012, and is a type of iron-dependent lipid peroxidation ( 5 ). With the advancements in research, ferroptosis has been reported to play a role in the development of blood diseases, neurological diseases, respiratory diseases, cardiovascular diseases, reproductive system diseases and tumors ( 28 - 32 ). However, the related reports of the role of ferroptosis in urinary system diseases have mainly focused on renal failure and renal tumors ( 18 , 22 ), and to date, there is no relevant report available on the topic of urolithiasis, at least to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Cells undergoing ferroptosis cannot be rescued by chemical or genetic inhibitors of apoptosis or necroptosis, which indicates that ferroptosis is a distinct form of cell death ( 4 ). Ferroptosis has been investigated in many human diseases, such as neurodegenerative diseases [including Parkinson’s disease ( 5 , 6 ), Alzheimer’s disease ( 7 , 8 ), Friedreich’s ataxia ( 9 ), and Huntington’s disease ( 10 )], organ injury [including hepatic damage ( 11 , 12 ), brain injury ( 13 15 ), spinal cord injury ( 16 , 17 ), and kidney injury ( 18 20 )], organ fibrosis ( 21 23 ), cardiovascular diseases ( 24 , 25 ), and gynecological diseases ( 26 28 ). Recently, an increasing number of studies on ferroptosis have been conducted in diverse cancers as ferroptosis is gradually being recognized as a potential form to eliminate cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Iron can serve as an essential signaling molecule that modulates diverse physiological processes, and iron homeostasis is required for the normal growth and development of the placenta and fetus during pregnancy (13, 63). An extensive body of evidence indicates that while iron deficiency is linked to abnormal pregnancy (13) and increased risk of fetal death (64), iron overload is associated with the manifestation of PCOS (65). Previous findings by Kim and colleagues indicate that increased circulating iron levels are associated with metabolic abnormalities, including HAIR, in PCOS patients (66).…”
Section: Discussionmentioning
confidence: 99%
“…For example, suppression of glutathione (GSH) biosynthesis and subsequent inhibition or degradation of glutathione peroxidase 4 (Gpx4) activity, disturbed balance of iron homeostasis, and activation of the mitogen-activated protein kinase (MAPK) signaling pathways all contribute to regulate the initiation and execution of ferroptosis (6, 7, 10, 11). However, little is known about the role of ferroptosis (13) in comparison with other forms of programmed cell death such as apoptosis (14, 15) in female reproduction.…”
Section: Introductionmentioning
confidence: 99%